2018
DOI: 10.17747/2078-8886-2018-3-66-79
|View full text |Cite
|
Sign up to set email alerts
|

Fourth Industrial Revolution: What Competences Are Necessary for Employees?

Abstract: The fourth industrial revolution has considerable impact on labor market transformation – professions, approaches to workchange. Already today the success of the company in many respects depends on ability of her employees to use technologies, and in particular, to do it creatively and innovatively.On the basis of empirical data it is analysed as far as the staff of the Russian companies feels influence of the new industrial revolution, what skills are necessary for adaptation in the conditions of digital tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 4 publications
0
3
0
1
Order By: Relevance
“…Table 2 shows that the value of the Bartlett test is significant (p-value<0.05). The KMO adequacy measure value is 0.927, which is above the minimum value of 0.6, indicating that Bartlett test is significant [26], [29], [30]. The KMO value shows that the value was greater than 0.6 and close to 1.0 and Bartlett's test significance value close to 0.0 indicates that the data is adequate and appropriate for next reduction procedure [23], [24].…”
Section: Efa For Personal Effectiveness Competencies (Pec) Constructmentioning
confidence: 88%
See 2 more Smart Citations
“…Table 2 shows that the value of the Bartlett test is significant (p-value<0.05). The KMO adequacy measure value is 0.927, which is above the minimum value of 0.6, indicating that Bartlett test is significant [26], [29], [30]. The KMO value shows that the value was greater than 0.6 and close to 1.0 and Bartlett's test significance value close to 0.0 indicates that the data is adequate and appropriate for next reduction procedure [23], [24].…”
Section: Efa For Personal Effectiveness Competencies (Pec) Constructmentioning
confidence: 88%
“…The measure of reliability instruments is estimated through Cronbach's alpha values [23], [26]. The Cronbach's alpha value of an instrument must exceed the minimum limit of 0.7 to be used in the next phase [24], [29]. PEC construct has indicated that professional as the component 1 followed by component 2 which independent and confident and third component which is passion.…”
Section: Efa For Personal Effectiveness Competencies (Pec) Constructmentioning
confidence: 99%
See 1 more Smart Citation
“…Op deze manier leren studenten namelijk een essentiële (21e eeuwse) vaardigheid voor de toekomst. Kunnen samenwerken, interpersoonlijke vaardigheden en teamwork staan op zowel de verlanglijstjes van werkgevers (Bramucci, Litman, McGuire, McNeil & Brown 2000;Kondratyuk, 2018) als die van beleidmakers in het onderwijs (Aabla, 2017;Humburg & van der Velden, 2013). Ook maatschappelijke ontwikkelingen zoals groeiende onzekerheid, globalisering en de klimaatcrisis vragen om burgers die goed kunnen samenwerken met elkaar.…”
Section: Probleem En Contextunclassified